Effectiveness of libraries in supporting researchers' information needs: The impact of a digital library - Ayob, Arinawati; Abdul Rahman, Habsah (2010)
As one of the supporting departments of a university, the academic library plays a vital role in providing essential information resources and services to the researchers. Changes in information technology have impacted libraries due to change in the format of information resources and the information seeking behavior of users. Technology has transformed the way researchers seek, obtain and use information. Libraries therefore need to critically examine their effectiveness and continuously support researchers in fulfilling their research needs. Research has been conducted at an academic library that is moving towards transforming traditional services to a highly digital environment. The fruition of this idea is blooming into reality with the almost completed research wing of the library. In preparation of ensuring suitable and relevant research information, the research analyzed the effect and impact of digital information services existing so far. Moving from here the research hopes to further enhance facilities, services and training with special focus on academic clientele. Research results will be discussed in the course of this paper’s discussion. Amongst factors studied are the relationship between demographic characteristics and the perceived effectiveness of library services among researchers.